The problem of the quality of judging in rhythmic gymnastics - V.V. Perederij (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The aim of the study is to develop a classification of factors influencing the quality of judging in rhythmic gymnastics. As a result of consolidation of theoretical information and practical experience was a list of the factors that negatively affect the behavior of judges in gymnastics, which were divided into two groups: the objective and non-objective (subjective). Objective factors include intense competition schedule, fatigue, especially memory, attention, competition rules, to the subjective: the ratio of judges to their gymnast (team) or to the opposing team, the lack of interest in the performance, composition of the judging panel, the influence of authority and popularity sportswomen dependence on its management. Respondents were unanimous in that independent professional judges are needed in a rhythmic gymnastics. It is set that 64% respondent mark the presence of pressure on judges from the side of competitors.